I RESTARTED A JOKE: A BORGEAN APPROACH TO HUMOUR TRANSLATION - Gonçalves, Davi (Revista (Entre Parênteses), 2017)
Reflecting upon literature and literary translation, one can conclude that the autonomy Borgean critique bestows the latter functions perfectly vis-à-vis the requisites of humorous discourses and of their effects in other contexts. If there is no way to separate literature from the locale wherefrom it emerges, the same could be said about literature when (re)produced in a distinct chronotope. The literary is attached to the material just as the mind is inseparable from the matter. Literature, when translated, operates as the snowball effect. Since the departure, on the top of the mountain, the snowball moves forward, enhancing its broadness and its impact, while every place it goes through both affects and is affected by it. The hill whereby it slips does not have a bottom; the communication of literature never stops.